Molecular recognition of sialoglycans by streptococcal Siglec-like adhesins: toward the shape of specific inhibitors. Issue 6 (4th November 2021) - Di Carluccio, Cristina; Forgione, Rosa Ester; Bosso, Andrea; Yokoyama, Shinji; Manabe, Yoshiyuki; Pizzo, Elio; Molinaro, Antonio; Fukase, Koichi; Fragai, Marco; Bensing, Barbara A.; Marchetti, Roberta; Silipo, Alba
Abstract : We here present a detailed molecular description of sialoglycans recognition by Siglec-like adhesins from  S. gordonii  opening the venue for the design of specific inhibitors to influence the propensity of streptococci to cause infective endocarditis. Abstract : Streptococcus gordonii and Streptococcus sanguinis, commensal bacteria present in the oral cavity of healthy individuals, upon entry into the bloodstream can become pathogenic, causing infective endocarditis (IE). Sialic acid-binding serine-rich repeat adhesins on the microbial surface represent an important factor of successful infection to cause IE. They contain Siglec-like binding regions (SLBRs) that variously recognize different repertoires of O -glycans, with some strains displaying high selectivity and others broader specificity. We here dissect at an atomic level the mechanism of interaction of SLBR-B and SLBR-H from S. gordonii with a multivarious approach that combines NMR spectroscopy and computational and biophysical studies. The binding pockets of both SLBRs are broad enough to accommodate extensive interactions with sialoglycans although with key differences related to strain specificity. Furthermore, and significantly, the pattern of interactions established by the SLBRs are mechanistically very different from those reported for mammalian Siglecs despite them having a similar fold. Thus, our detailed description of the binding modes of streptococcal Siglec-like adhesins sparks the development of tailored synthetic inhibitors and therapeutics specific for Streptococcal adhesins to counteract IE, without impairing the interplay between Siglecs and glycans.